Educação para a sexualidade: intervenção em um grupo de adolescentes assistidos pelo cras, a partir do conhecimento de suas representações sociais em relação às DST/Aids - Christovam, Amauri Rogério; Thomazelli, Caroline; Frabetti, Karol Conti; Moretto, Laísa Aparecida [UNESP]; Silva, Nilma Renildes da [UNESP] (My University, 2012)
The Socio-Historical Psychology Theory understands human development constituted by the social and historical relations, in whom the individual belongs, and understanding the meaning of adolescence as a time and built. The social psychology, in this theoretical approach, proposes, among others, the category Social Representations (SR) for analysis and discussion of psychosocial phenomena. This study aimed to investigate the SR of adolescents about sexually transmitted diseases (STD/SIDA), by means of a questionnaire in order to know their vulnerabilities to spread of STD/SIDA. After the identification of vulnerabilities, an intervention was performed through a group processes with adolescents 11 to 15 years, users of services CRAS of a city in São Paulo State, to provide subsidies in relation to education for sexuality. Based on data collected and discussed, it can be stated that among the multiple determinants of the increased incidence, as the Epidemiological Bulletin 2011/MS, the lack of safe sex practices contributes to the vulnerability of adolescents. Emphasizes the need to know their Social Representations proposing an intervention, not to reproduce the imposition of „packages awareness of safe sex practices,” homogeneous and universal, it does little to promote health and education of adolescents.

A Teoria Psicológica Sócio-Histórica compreende o desenvolvimento humano como constituído nas e pelas relações sociais e históricas, sendo a adolescência um momento significado e construído - logo, histórico. A Psicologia Social, nesta abordagem teórica, propõe, entre outras, a categoria Representações Sociais (RS) para análise e discussão dos fenômenos psicossociais. Este trabalho objetivou investigar as RS de adolescentes sobre Doenças Sexualmente Transmissíveis (DST/AIDS) por meio de um questionário, visando conhecer suas vulnerabilidades ao contágio das DST/AIDS. Após essa identificação, foi realizada uma intervenção, por meio de um grupo focal com adolescentes de 11 a 15 anos, usuários dos serviços do CRAS de uma cidade do interior paulista, a fim de oferecer subsídios em relação à educação para a sexualidade. Conforme os dados coletados e discutidos, pode-se afirmar que, dentre as múltiplas determinações do aumento da incidência de DST/ AIDS, conforme o Boletim Epidemiológico de 2011/MS, o desconhecimento sobre práticas sexuais seguras contribui para a vulnerabilidade de adolescentes. Enfatiza-se a necessidade de conhecer suas RS ao propor uma intervenção, para que não se reproduzam imposições de “pacotes de conscientização de práticas sexuais seguras” de maneira homogênea e universal, que pouco contribui na promoção à saúde.
Education for sexuality: intervention in a group of adolescents assisted by crass, from knowledge of their social representations in relation to STD/ SIDA
Keywords: Social representations; Adolescence; Education for sexuality; Representações sociais; Adolescência; Educação para a sexualidade